Analysis of Completeness Filling in the Informed Consent Formulir at Bhakti Husada General Hospital, Krikilan, Banyuwangi, East Java - Putra, Muhammad Dudayev Caesar; Murti, Bhisma; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: The quality and success of medical record unit services can be seen from the management of the units that have been carried out by professional staff. The minimum service standard for the medical record unit for completing informed consent is 100%. Completeness of filling out informed consent at the Bhakti Husada Krikilan Banyuwangi General Hospital from April to June is still not in accordance with the SPM, namely 79.33%. The aim of this research is to analyze the completeness of filling out informed consent at Bhakti Husada Krikilan Banyuwangi General Hospital.Subjects and Method: This research is a qualitative research with a case study approach conducted at Bhakti Husada Krikilan General Hospital, Banyuwangi, East Java. The sampling technique used was purposive sampling. Data collection techniques using interviews, observation, documentation and questionnaires. Test the validity of the data using triangulation.Results: The percentage of completeness of filling out the informed consent sheet at the Bhakti Husada Hospital from May to July 2022 is 15.28%. The lowest percentage lies in the content and authentication section. Management elements that affect the incomplete filling of informed consent include man factors (knowledge and years of service), machine (availability of office stationery, monitoring and evaluation), method (standard operating procedures) and money (rewards and salaries). In addition, it was also found that busy work schedules and emergency cases could affect the incomplete filling of informed consent.Conclusion: The percentage of completeness of filling out informed consent at Bhakti Husada Krikilan Hospital is low. Elements of management that influence are man factors (knowledge and years of service), machine (availability of office stationery, monitoring and evaluation), method (standard operating procedures) and money (rewards and salaries).Keywords: Medical Records, Completeness of Informed Consent, Quality of Medical Record UnitsCorrespondence: Muhammad Dudayev Caesar Putra. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: muhammadnewduda-yev@gmail.com. Mobile: 085706450991.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.01.08